An algorithm for testing whether a regular language is a code - Hân, Nguyễn Đình; Vinh, Hồ Ngọc; Huy, Phạm Trung; Vân, Đỗ Long (Journal of Computer Science and Cybernetics, 2012)
We present an extension of the test proposed by Sardinas and Patterson (1953) for deciding whether a set of words is a code. As a consequence, we obtain an effective algorithm that decides in ${\cal O}(k)$ time whether a given regular language is a code, where $k$ is the finite index of the syntactic congruence of this language.